A superdotação na primeira infância sob a perspectiva das políticas públicas em educação especial - Castro, Meire Luiza de (2020)
This research arose from the need, as an education professional, to provide specialized care to children with high skills / giftedness (AH / SD) in Early Childhood Education. In this way, the general objective is to contribute so that teachers can carry out the process of identifying giftedness in Early Childhood Education, as well as promoting specialized care alternatives so that students are adequately served in their areas of talent. As specific objectives, it is important to propose a study group through WhatsApp with the teachers of Early Childhood Education at the Center for Teaching and Research Applied to Education (CEPAE); identify gifted students in several areas (academic, psychomotor, artistic, among others); to contribute with new teaching possibilities through differentiated pedagogical interventions; and to present a training proposal through the realization of short courses to, when possible, be put into practice in the school institution itself. Taking advantage of this, this master's research aimed to prepare teachers to recognize the indicators of high skills / giftedness in children in Early Childhood Education and to analyze different conceptions of teaching that meet the real learning needs of these students, according to the legislation in force. , and thus favor its full development. To this end, I worked with CEPAE Early Childhood Teachers through an action research following five steps: elaborating, with the coordination of the Child Education Department (DEI), strategies for carrying out field research; welcoming teachers and applying a survey questionnaire (prior knowledge on the issue of giftedness in early childhood education); conducting mini-courses on aspects of child development and learning and the general characteristics presented by the gifted and talented; observation of indicators of high skills / giftedness in early childhood children enrolled in the DEI; and meeting with professors participating in the research to debate and reflect on the proposal presented. The results indicated that children differ in their way of being and need a differentiated curriculum that, in fact, meets their particularities. In addition, it was possible to understand how important the training process is in order to identify and assist children with high potential. From this research, the Educational Product was obtained, which was the Teacher Training Manual for Identification and Pedagogical Practices of Assistance to High Potential Children in Early Childhood Education.